"Uso del nutriente translaminar, en el desarrollo vegetativo del banano (Musa AAA.) variedad williams Cantón Valencia, Los Ríos". - Rivas Toapanta, Kleiner Orlando (2020)
This research was carried out at the “San Carlos de Chillovado” farm owned by Mr. Carlos Pérez, Valencia canton, which is located in the north of the Province of Los Ríos km13 via Quevedo, in the coastal region of the country, The objectives were: Evaluate the effect of translaminar fertilization on plant height, Determine the effects of translaminar fertilization on pseudostem diameter, and Select the best dose and frequenc